The mitochondrial genomes of sponges provide evidence for multiple invasions by Repetitive Hairpin-forming Elements (RHE) - Erpenbeck, Dirk (BioMed Central, 2009)
BACKGROUND: The mitochondrial (mt) genomes of sponges possess a variety of features, which appear to be intermediate between those of Eumetazoa and non-metazoan opisthokonts. Among these features is the presence of long intergenic regions, which are common in other eukaryotes, but generally absent in Eumetazoa. Here we analyse poriferan mitochondrial intergenic regions, paying particular attention to repetitive sequences within them. In this context we introduce the mitochondrial genome of Ircinia strobilina (Lamarck, 1816; Demospongiae: Dictyoceratida) and compare it with mtDNA of other sponges. RESULTS: Mt genomes of dictyoceratid sponges are identical in gene order and content but display major differences in size and organization of intergenic regions. An even higher degree of diversity in the structure of intergenic regions was found among different orders of demosponges. One interesting observation made from such comparisons was of what appears to be recurrent invasions of sponge mitochondrial genomes by repetitive hairpin-forming elements, which cause large genome size differences even among closely related taxa. These repetitive hairpin-forming elements are structurally and compositionally divergent and display a scattered distribution throughout various groups of demosponges. CONCLUSION: Large intergenic regions of poriferan mt genomes are targets for insertions of repetitive hairpin- forming elements, similar to the ones found in non-metazoan opisthokonts. Such elements were likely present in some lineages early in animal mitochondrial genome evolution but were subsequently lost during the reduction of intergenic regions, which occurred in the Eumetazoa lineage after the split of Porifera. Porifera acquired their elements in several independent events. Patterns of their intra-genomic dispersal can be seen in the mt genome of Vaceletia sp.